COOPERATIVE PRINCIPLE IN NOVEL “DRUPADI” BY SENO GUMIRA AJIDARMA: GRICE’S PERSPECTIVE - Annisa, Luthf; Nurdiansah, Nandang; Masadi, M. Anwar (Annual International Conferences on Language, Literature, and Media, 2021)
This study discusses the flouting and violation of the cooperative principles in the novel "Drupadi" by Seno Gumira Ajidarma. The purpose of this study is to examine the utterances in the novel "Drupadi" by Seno Gumira Ajidarma those that apply and violate Grice’s cooperative principle (four maxims). The four maxims are the maxim of relation, the maxim of manner, the maxim of quality, and the maxim of quantity. This research collected data through the technique of reading and writing. The data analysis techniques are data reduction, data presentation, and conclusion. The results show that twelve words are included in the utterances that adhere to the cooperative principle. Six expressions obey the relevance/relational maxim, one expression obey the maxim of manner, four obey the quality maxim, and one utterance obey the quantity maxim. The researcher also found speeches that violated the cooperative principle as many as three words. Two utterances violate the quality maxim, and one utterance violates the quantity maxim, no utterance violates the maxim of the relevance and maxim of the way.